A STUDY OF RELATIONSHIP MARKETING IN COMMODITIES EXCHANGES LIKE MCX IN INDIA - Kothari, Silky (2007)
Marketing strategies can lead to success if implemented in the right way. Relationship marketing has been thought of as a new paradigm in marketing over the last few decades.It has been believed by academics and practitioners that companies can achieve success in the long run by maintaining relationship with their customers and business ssociates. However, much of the work and understanding of relationship or relational marketing to date focuses on the Western perspective, and hardly any work has been done in the Marketing of Indian Commodities Exchange context. The current literature on relationship marketing in the financial sector is relatively under-researched, and hence this dissertation aims to present some insight into relationship marketing in this sector. The main objective of this research is to unravel the nature of relationship marketing applied in the Commodities Exchanges like MCX, its benefits and key factors.